Effects of Different Biochars on Cd Immobilization in Rice Paddy Soil: A Two-year Field Study - Haochuan Ge; Fengfeng Sui; Yangqiong Pu; Guixiang Quan; Liqiang Cui; Jinlong Yan (BioResources)
This study addressed the efficiency of different biochars in Cd immobilization in soil. An acidic sandy loam paddy contaminated with Cd was selected for the field trial, which was continued for three rice-growing seasons. Rice straw biochar (BR), wheat straw biochar (BW), and maize straw biochar (BM) were pyrolysed as pellets at 450 °C and applied at 0 t/ha (BC0), 10 t/ha (BR1/BW1/BM1), and 20 t/ha (BR2/BW2/BM2). Compared to BC0, BR and BW were more effective in decreasing Cd accumulation in rice grains, and BR2 achieved the highest reduction, averaging 43.4% over three rice seasons. The Cd contents in rice roots with BR2 treatment decreased by 15.2 to 55.3% compared with BC0. The bioconcentration factors for grains (BCFGrain), shoots (BCFShoot), and (BCFRoot) of BR2 treatment were averagely decreased by 53.3%, 27.4%, and 19.0% over BC0, respectively. There was a negative correlation between soil CaCl2-Cd and soil pH. FTIR analysis demonstrated that Cd complexed with SiO2 on aged BR2 particles. During the natural aging process, BR2 significantly and sustainably inhibited rice uptake Cd through co-deposition. Therefore, the BR was judged to be an effective soil amendment with high Si content and alkalinity for Cd immobilization in paddy soil.